Des dispositifs en ligne pour personnaliser l'apprentissage tout au long de la vie : quelques recommandations - Louise Sauvé (Centre National d'Enseignement à Distance, 2014)
Personalized lifelong learning is not just about giving learners a variety of learning resources, technologies for communication and collaborative work in a more or less structured environment. Foremost it is a questioning of the very notion of personalized learning and then identifying the guiding principles. Then it's the operationalization of these principles and their experimentation with learning devices in the context of personalized lifelong learning (formal and informal). Finally, guiding the designers/teachers and the training policymakers on the conditions to be put into place for a successful implementation of such devices. This text is an overview of the innovative experiments conducted by research teams under the supervision of SAVIE. The following areas will be discussed: taking into account the learner's background, the type of learning resources to be developed, organizing these resources into a personalized learning tool, help tools for design to facilitate the creation of such devices and the ergonomic principles to consider when designing these devices.